Perspective for Methicillin-resistant Staphylococcus Aureus colonization, Antibiotic Susceptibility Patterns and Risk factors for Colonization among People Living with HIV at Nyenga Hospital, Buikwe District, in Central Uganda - Ssenyonga Benedict; Mwebaze Sarah; Atuhairwe Christine; MugishaTaremwa Ivan (International Journal of Infection Prevention, 2018)
Background Colonization with methicillin-resistant Staphylococcus aureus (MRSA) is recognized as an association towards development of infections that may cause of morbidity among people living with Human Immunodeficiency Virus (PLWHIV). We report on the prevalence, antibiotic susceptibility pattern and risk factors associated with MRSA carriage among PLWHIV at Nyenga hospital, Buikwe district in central Uganda. Materials and Methods We conducted a cross-sectional study among PLWHIV attending Nyenga hospital anti-retroviral therapy (ART) clinic. Nasopharyngeal swab was collected from each participant, cultured to isolate Staphylococcus aureus, and drug susceptibility testing (DST) performed. Sociodemographic data and medical history was recorded. Results We enrolled 219 PLWHIV; of these, 58.4% (N=128) were females. The majority of participants (95.0%) were on ART. Ninety-eight (44.75%) of the nasopharyngeal swabs had growth, of which 41 (41.84%) were S. aureus. Of these, 11 (5.02%, 95% confidence interval: 3.67-7.02) were MRSA. Of 41 isolated S. aureus strains, only 8 (19.51%) were susceptible to all antibiotics tested. A total of three (7.32%) were multi-drug resistant (MDR), while one1 (2.43%) was a possible extensively drug resistant (XDR) strain. Deteriorating immunologic state as indicated by a low CD4 count showed a significant association with the MRSA colonization. Conclusion These results are reassuring that MRSA colonization is high among PLWHIV. As most of the antibiotics in use were resistant, it raises concerns of intricate clinical management in a low resource set up.
Keywords: MRSA